Study the Effect of Corrosion and Scale Inhibitors on Corrosion Rate of Carbon Steel in Cooling Towers Unit in Oil Refineries - Ali, Mazin Nabih (Al-Nahrain Journal for Engineering Sciences, 2021)
In the present work the effect of Corrosion & Scale Inhibitor was evaluated by using of the commercial product (Kurita S2050) that mainly containing of (Na2HPO4) sodium phosphate as corrosion inhibitor and (C6H11NaO7) sodium glocunate as scale inhibitor & dispersant. The dosing rate of this chemical was controlled according to the treatment system depend mainly on the monitoring of LI & RI indexes for (30) days treatment in the cooling tower unit of Al-Dora Oil refinery-Baghdad. The corrosion rate and the corrosion inhibitors efficiency were calculated by measurement of weight loss in standard test coupon (AISI 1010). After 30 day of the Field Test, the result show that the treatment program performance was effective in the corrosion & scale inhibition through an acceptable corrosion rate less than 0.018 in gmd. Also the result of corrosion rate was analyzed statistically by using of (ANN) to formulate a prediction equation to corrosion rate identification.